Strategic Outsourcing and Collaborative Supply Chain Management for Sustainable Value Creation in Manufacturing Companies - Paredes-Carrasco, L (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study explores how strategic outsourcing and collaborative supply chain management contribute to sustainable value creation in Chilean manufacturing firms. It connects with current literature by examining inter-organisational collaboration, process redesign and sustainability through outsourcing and network-based strategies.Design/methodology/approachA qualitative multiple-case study was conducted using semi-structured interviews and internal documents analysis. The study focuses on practices related to operational efficiency, circular economy and knowledge transfer.FindingsChilean manufacturing SMEs pursue sustainable efficiency through strategic outsourcing and selective automation. They face challenges in knowledge sharing and circular material management. However, they develop adaptive responses with key partners. These practices enhance economic, social and environmental value.Research limitations/implicationsThe research is context-specific and does not allow for statistical generalisations. Future studies could compare different sectors or regions. This would help assess the transferability of the proposed model.Practical implicationsThe findings provide guidance for SMEs seeking to improve their sustainability performance. They highlight the role of collaborative practices, outsourcing decisions and adaptive capabilities.Social implicationsThis research highlights how strategic outsourcing and collaboration in Chilean manufacturing SMEs produce tangible social outcomes. By engaging local suppliers, firms stimulate regional employment and promote inclusive labour practices. Circular optimisation and renewable energy adoption reduce negative environmental effects, improving community health and well-being. Knowledge transfer fosters collective learning, supporting social innovation and strengthening local production systems. Together, these practices promote responsible business conduct, enhancing societal trust in SMEs and reinforcing social cohesion. The study shows that sustainability-oriented collaboration can generate shared value that extends beyond firms, contributing to long-term development in emerging economies.Originality/valueThis study presents a novel SVC framework connecting underexplored theoretical gaps with empirical evidence. It contributes to the BPM field by demonstrating how process transformation and inter-organisational coordination support sustainable performance in SMEs.